‘Mil rochas e tal...!’ : inventário dos sítios da arte rupestre do Vale do Côa (2.ª parte) - Reis, Mário (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
Since its discovery, and from its public announcement in late 1994, the rock art of the Côa valley has not ceased to increase its numbers, which are reflected at this point in almost 80 sites, with a quantity of engraved rocks that exceeds one thousand records. In parallel, the diversity of these sites and records has also increased remarkably. In the first part of this paper we presented a description of the Côa rock art sites distributed over the valley of this river. In this second part we present a description of the remaining sites of this huge rock art complex, contemplating now those distributed on the banks of the Douro river, along both sides of the mouth of the Côa.